MENTORING THE TROUBLED WOMEN WORKERS AT THE INDONESIAN EMBASSY IN SINGAPORE: Integration of Sufism and Psychology - Amin Syukur; Nidhomun Ni'am; Sri Rejeki (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2016)
There are five components ofdemographics, namely; birth, death, migration, social mobility, and marriage. This study focuses onthe migration of people, commonly called circular migration. Population growth and economic issues, namely the narrowness of employment in Indonesia and the salary promised to be the cause. In Indonesia, this migration is called Indonesian Workers (TKI), both menand women.The majority of Indonesian people's livelihood is asrice farmers, whose results are not sufficient.Naturally, the majority of the Indonesian people become motivated to work abroad. This study focuses on one of the countries in Southeast Asia, namely Singapore with consideration of the number of Indonesian migrant workers who work in Singapore.